The impacts of metering and climate conditions on residential electricity demand the case of albania - Iimi, Atsushi (The World Bank, 2011)
Albania is among the most vulnerable countries to external energy shocks and climatic conditions, because of its high dependency on hydropower for electricity. Given highly volatile international energy prices and expected global warming, it is becoming increasingly important to manage the demand for electricity. However, the country has long been faced with a significant problem of electricity metering. About one-third of total energy is lost for technical and nontechnical reasons. This paper estimates the residential demand function by applying a two-stage system equation method for an endogenous censored variable, because the lack of metering makes the electricity consumption partially observable for the econometrician. It is found that metering is important to curb non-essential electricity use by households. The electricity demand could also be reduced by raising the first block rate and lowering the second block rate and the threshold between the two blocks. In addition, weather conditions and home appliance ownership would affect the demand for electricity. But the latter looks more influential than the former